The Effect of Osborn’s Model on Developing Students’ Rhetoric Concepts - Harara, Nour Mohammad; Amarneh, Emad Farouq; Hammouri, Raid N. Al; Rababah, Mahmoud Ali; Rababah, Luqman; El-Omari, Abdallah Hussein (Journal of language teaching and research, 2024)
This study examines the effect of teaching a school rhetoric unit employing Osborn's (1963) model. The study sample consisted of 70 Jordanian eleventh-grade students, with 35 in the experimental group and 35 in the control group. Two instruments were used to collect data: a scale designed according to Osborn's model and an achievement test. The school unit of rhetorical concept development was applied to six classes over six weeks in the experimental group, while the control group was taught using the standard method. The findings showed statistically significant differences in favour of the experimental group, with means of 76.66 and 66.15, respectively. The t-test value was 13.02, statistically significant at a significance level 0.01. The impact percentage was calculated at 92%, indicating a statistically significant result according to the Karl formula. Therefore, this percentage is a positive indicator of the effectiveness of using the Osborn model for the conceptual development of the experimental group of students. Based on the findings, the study recommends using this model for teaching rhetoric and literary criticism in other school classes.